Pollution Management and the Making of Prosperous Cities - World Bank (World Bank, Washington, DC, 2020)
The work summarized in this report fills a knowledge gap by contributing to an improved understanding of the links between competitiveness and pollution. Specifically, it argues that pollution need not be an inevitable consequence of development. Indeed, there are examples of cities that have been able to manage pollution while transitioning through different development stages. Recognizing, however, that policy makers are often grappling with how to negotiate this balance, the report also provides policy makers with options to strengthen competitiveness in their cities while mitigating the negative effects of pollution. This report summarizes the findings of the Pollution Management and the Making of Prosperous Cities Program, which had a three part objective: (i) to generate information and knowledge that will be helpful to mayors and other city and national level decision makers in urban planning and economic competitiveness; (ii) to increase understanding and capacity among pollution related decisionmakers; and (iii) produce outputs and tools to support policy makers in managing both pollution and competitiveness. In order to build a knowledge base around the links between competitiveness and pollution, and provide policymakers with useful tools for decision making, this work uses new empirical evidence, city case studies, and international best practices.